Effects of art-based mandala intervention on distress and anxiety in cancer patients - KARABUĞA YAKAR, HATİCE (ELSEVIER SCI LTD, 2021)
Objective: This study was planned to determine the effect of art-based mandala intervention on the distress and anxiety experienced by cancer patients. Methods: This semi-experimental study with a single group pretest-posttest design was performed with 12 breast cancer survival patients. The data were collected through Patient Diagnostic Form, Distress Thermometer, Trait Anxiety Inventory. Patients participated in the Art-Based Mandala Intervention for eight weeks, one day a week, 2 h each. The distress and anxiety levels of the patients were measured before starting the program and at the end of the program. Results: Cancer patients experienced moderate level of anxiety (50.66 +/- 6.91) and clinically significant distress (4.08 +/- 2.74). Anxiety scores of cancer patients decreased significantly after the program compared to before the program (p < 0.05). The distress scores of cancer patients increased after the program compared to before the program (p > 0.05). Conclusion: After the art-based mandala intervention program, anxiety scores of breast cancer survival patients decreased, and distress scores increased.
Keywords: Anxiety; Art-based intervention; Cancer patient; Distress; Mandala; BREAST-CANCER; PSYCHOLOGICAL DISTRESS; SURVIVORS; RECURRENCE; THERAPY; FEAR; DIAGNOSIS